The End of time : the Mayan prophecies revisited - Gilbert, Adrian (Edinburg, New York : Mainstream Publishing, 2006)
According to the ancient Maya, the world as we know it will end on 22nd December, 2012. On that date, their calendar will click round to zero for the first time in over 5,000 years. They prophesised that this destruction will be preceded by a series of natural disasters, including earthquakes and floods. Does this sound familiar? What will this mean for us? Should we take seriously their claims that this will be a time of apocalyptic cataclysm? And, just how did the Maya, a clever but nonetheless Stone Age people, calculate the date of an astronomical event that would take place many millennia in the future? These are just some of the questions posed by Adrian Gilbert, co-author of the international bestseller "The Mayan Prophecies". In "The End of Time", he revisits the ancient archaeological sites of the Maya and makes astonishing new discoveries about their cosmology. He also makes use of modern computer technology to 'backtrack' the skies to the way they would have appeared in previous ages, which has resulted in some major findings concerning the astronomical significance of the Mayan calendar. This absorbing, thought-provoking book is enhanced by a number of illustrations and photographs to help explain the many theories and ideas conveyed in the text. And, in case, an apocalyptic event really is upon us, the author offers tips for survival.
Mexico revisited -- The City of the dead -- The Rolls of time -- The Rediscovery of the Maya -- Decoding the Maya legacy -- A New vision of the Maya creation -- Astronomy and the death of seven Macaw -- Journeys from the East -- The Aztecs and Atlantis -- The Serpent cult and the planetary Gods of the Maya -- At the end of the age -- Cycles of the sun
Keywords: MAYA ASTRONOMY